FACING THE AISLE NAVIGATING CHALLENGES IN THE GENERAL STORE BUSINESS - Dwivedi, Seema; Singh, Chandan; Agarwal, Pranjal; Soni, Kartik; Tripathi, Shivam Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
General stores, once the backbone of local economies, now confront a plethora of challenges in today's rapidly evolving retail landscape. This abstract explores the multifaceted hurdles faced by general store businesses and offers strategic insights to navigate them effectively. Evolving consumer preferences represent a significant challenge, as shoppers increasingly prioritize convenience, sustainability, and value. Moreover, the rise of e-commerce giants intensifies competition, compelling general stores to differentiate themselves through unique offerings and personalized customer experiences. Operational efficiency emerges as another critical concern, with general stores needing to optimize processes, manage inventory effectively, and invest in employee training to remain agile and cost-effective. Furthermore, community engagement plays a pivotal role in maintaining relevance and fostering brand loyalty, necessitating active involvement in local events, sponsorships, and partnerships. Navigating regulatory complexities is paramount, with general stores needing to stay abreast of evolving legal requirements, obtain necessary permits, and adhere to stringent food safety standards. By embracing innovation and leveraging technology, general stores can enhance customer experiences, streamline operations, and expand their reach beyond traditional brick-and-mortar confines.